2017
DOI: 10.1007/s11165-017-9628-0
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Science Progression in School Year 1–9: a Case Study of Teachers’ Suggestions and Rationales

Abstract: The inclusion of nature of science (NOS) in science education has for a long time been regarded as crucial. There is, however, a lack of research on appropriate NOS aspects for different educational levels. An even more neglected area of research is that focusing on teachers' perspectives on NOS teaching at different levels. The aim of this article is to examine NOS progression in the light of teachers' suggestions and rationales. In order to obtain teachers' informed perspectives, we chose to involve six teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“…It is generally agreed that IBST cannot be achieved if students are not helped to acquire informed views of NOS (Billingsley & Fraser, 2018;Das et al, 2019;Fernandes et al, 2018;Herman et al, 2019;Leden & Hansson, 2019;Lederman et al, 2002). This is because views of NOS have been found to influence how science is conducted, accepted and interpreted (Das et al, 2019;Lederman et al, 2013;Liang et al, 2008;Temel et al, 2018).…”
Section: Nosmentioning
confidence: 99%
“…It is generally agreed that IBST cannot be achieved if students are not helped to acquire informed views of NOS (Billingsley & Fraser, 2018;Das et al, 2019;Fernandes et al, 2018;Herman et al, 2019;Leden & Hansson, 2019;Lederman et al, 2002). This is because views of NOS have been found to influence how science is conducted, accepted and interpreted (Das et al, 2019;Lederman et al, 2013;Liang et al, 2008;Temel et al, 2018).…”
Section: Nosmentioning
confidence: 99%
“…Several elements of NOS concepts have already been integrated to science education curricula at all grade levels by developed countries. However, there are only a limited number of research studies uncovering NOS conceptions of younger children, especially at pre-K level and identifying the most suitable components of NOS for different grade levels (Bell & Clair, 2015;Leden & Hansson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Challenges connected to NOS teaching have been thoroughly investigated and has contributed explanations as to why there is a perceived gap between research intentions and classroom practice (e.g., Abd-El-Khalick et al 1998;Akerson and Hanuscin 2007;Brickhouse and Bodner 1992;Clough and Olson 2012;Lakin and Wellington 1994;Hodson 1993;Höttecke and Silva 2011;Leden et al 2015;Lederman 1995). In other articles (Leden et al 2015;Leden and Hansson 2017), we have reported on, and argued that, teachers' perspectives constitute an important part in the attempt to understand and examine this gap further. In the present study, we continue our exploration of teachers' perspectives.…”
Section: Discussionmentioning
confidence: 86%
“…For a detailed description of these teachers' discussion of age-appropriate NOS teaching, see Leden and Hansson (2017).…”
Section: Teachers' Suggestions Of Relevant Issuesmentioning
confidence: 99%